Identifikasi Kandungan Rhodamin B Pada Lipstik Yang Beredar Di Pasar Tradisional Kabupaten Mamuju - Nurmadina; Nini Sahrianti S; Saharuddin; Akbar Nur (Journal Kiara : Nursing and Midwifery, 2024)
Rhodamin b can irritate the respiratory tract and is also carcinogenic or stimulate the growth of cancer cells and damage the liver if used continuously. This study aims to determine the presence of Rhodamine B content in lipsticks that are circulating in the old market and the new market in Mamuju Regency. This research is a qualitative descriptive study with laboratory testing using the KIT test and organoleptic observation with a total sample of 9 samples who do not have a BPOM permit. Based on the results of the organoleptic observation, there were 8 samples that had different colors. of the eight samples have different colors and textures that are solid and homogeneous. Observation results using a test kit from 9 samples, 8 samples were positive for rhodamine B and 1 sample was negative. The positive sample brands are S.A miss gird, S.C bulberry, S.D alovera, S.E baby lip, S.F maybellin, S.G loves me, S.H mini lip, S.I ya geul. And the sample brands that are negative are S.B, Saudi Arabia green. Suggestions for consumers to be more careful in choosing cosmetics / lipstick products. Of the nine samples that were examined, only 1 sample was negative and 8 other samples were positive. This shows that there are still many lipsticks circulating in the traditional market that contain Rhodamine B. Analysis using the Rhodamine B test kit.